M-ABRC (Adaptive Binary Range Coder) using Virtual Sliding Window technique and its VLSI implementation - Mrudula, S.T.; Srinivasa Murthy, K.E.; Giri Prasad, M.N. (Microprocessors and microsystems, 2019)
Arithmetic coding is the data compression techniques, which encodes the data by generating the code string that represents a functional value between 0 and 1. In this paper, we propose a modified-Adaptive Binary-RC (Range Coder) or M-ABRC. Our algorithm minimizes the multiplication bit capacity through introducing the VLSI architecture, proposed algorithm uses the LUP (Look UP Table)-VSW (Virtual Sliding Window) for the probability estimation. In order to achieve the higher compression rate, our method M-ABRC has been implemented, this in terms provides the better adoption probability in encoding phase and also gives the absolute estimation of low-EBS(entropy binary sources). Moreover In order to evaluate the algorithm we have compared with the several existing technique, comparison takes place based on the two parameter i.e. device utilization and the power dissipation (static and dynamic).